Genetic Animal Models of Cardiovascular Pathologies - Mikhail Blagonravov; Anna Ryabinina; Ruslan Karpov; Vera Ovechkina; Maxim Filatov; Yulia Silaeva; Sergei Syatkin; Enzo Agostinelli; Vsevolod Belousov; Andrey Mozhaev (Biomedicines)
This review critically examines the evolving landscape of genetic animal models for investigating cardiovascular diseases (CVDs). We analyze established models, including spontaneously hypertensive rats, Watanabe hyperlipidemic rabbits, etc., and transgenic models that have advanced our understanding of essential and secondary hypertension, atherosclerosis, and non-ischemic diseases of the heart. This review systematically evaluates the translational strengths and physiological limitations of these approaches across species barriers. Particular attention is paid to emerging technologies—AAV-mediated gene delivery, CRISPR-Cas9 editing, and chemogenetic tools—that enable unprecedented precision in manipulating cardiac-specific gene expression to study pathophysiological mechanisms. We address persistent challenges including off-target effects and transgene expression variability, while highlighting innovations in synthetic vectors and tissue-specific targeting strategies. This synthesis underscores how evolving genetic technologies are revolutionizing cardiovascular research paradigms, offering refined disease models and optimized therapeutic interventions that pave the way toward personalized medicine approaches for the world’s leading cause of mortality.